PENGARUH KEPEMILIKAN INSTITUSIONAL, PERTUMBUHAN PENJUALAN DAN PERTUMBUHAN LABA TERHADAP KEBIJAKAN DIVIDEN - Napitupulu, Lidia Sinta; Azzahra, Khoirunnisa (JURNAL AKUNTANSI BARELANG, 2024)
This research aims to provide empirical evidence that there is an influence of Institutional Ownership, Sales Growth and Profit Growth on Dividend Policy. This research uses a quantitative approach and the data used is secondary data. The population in this research is Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange for the period 2018 - 2022. The method for determining the sample uses purposive sampling. A sample of 11 companies was obtained over a 5 year period. The data analysis technique used is multiple linear regression analysis with the help of e-views version 12 statistical data processing. The results of the F test show that Institutional Ownership, Sales Growth and Profit Growth have a significant effect on Dividend Policy. The t test results show that Institutional Ownership has an effect on Dividend Policy, Sales Growth has an effect on Dividend Policy and Profit Growth has no effect on Dividend Policy.